IMPLEMENTASI NILAI-NILAI MINHAJUL ‘ABIDIN DALAM PENDIDIKAN KARAKTER PADA ERA DIGITAL - Khairunnisa Ulfadhilah; Meiza Fajar Akbar; Anam Khoirul Rozak (Hamka Ilmu Pendidikan Islam, 2025)
Character education in today's digital era faces unique challenges, especially in the formation of moral and ethical values of the younger generation. One of the approaches that can be adopted to overcome this problem is the implementation of Minhajul Abidin values, which are guidelines for life based on Islamic teachings and can provide a solid foundation in character development. Through a literature study, this study aims to explore how Minhajul Abidin's values can be integrated in character education, especially in the context of formal and non-formal education in a digital environment. Research shows that values such as honesty, discipline, responsibility, and compassion can be a solid foundation in shaping students' character in the midst of the onslaught of information and technology that often triggers identity crises. By leveraging existing digital platforms, such as social media and learning apps, educators have the opportunity to instill these values in an engaging and relevant way. In addition, this approach also allows collaboration between parents, teachers, and the community in creating an environment that supports the consistent application of Minhajul Abidin's values. The results of the literature studied show that by strengthening these values in the educational curriculum, not only can students' character be formed, but also they will be better prepared to face complex global challenges. Through effective implementation, it is hoped that Minhajul Abidin-based character education can help create a generation that is not only academically intelligent, but also has strong personalities and noble ethics. This research contributes to the development of character education models in the digital era by making spiritual and moral values the main foundation.